2004
DOI: 10.1007/s00109-004-0556-x
|View full text |Cite
|
Sign up to set email alerts
|

Lack of association of polymorphisms of the lymphotoxin ? gene with myocardial infarction in Japanese

Abstract: Vascular inflammation plays an important role in the development of myocardial infarction (MI). Lymphotoxin alpha (LTA) is a cytokine with multiple functions in regulation of the immune system and inflammatory reactions. The aim of this study was to examine whether polymorphisms of the LTA gene are associated with the risk of MI in Japanese men and women. A case-control association study was performed for the 252A-->G and 804C-->A polymorphisms of the LTA gene and the prevalence of MI. The study population com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
45
1
3

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 21 publications
7
45
1
3
Order By: Relevance
“…Associations between a non-synonymous LTA variant (T60N) and type 2 diabetes have recently been reported in Danish and Japanese subjects [14,15]. In these studies, the rare homozygous T60N (AA) genotype was found to be associated with increased risk of disease.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Associations between a non-synonymous LTA variant (T60N) and type 2 diabetes have recently been reported in Danish and Japanese subjects [14,15]. In these studies, the rare homozygous T60N (AA) genotype was found to be associated with increased risk of disease.…”
Section: Discussionmentioning
confidence: 99%
“…If allowance is made, under realistic models [22,23], for the increase in susceptibility allele frequency to be expected when, as in the present study, cases have been selected for familiality and early onset, these power values rise to 91 and >99%, respectively. In the specific case of T60N, where previous evidence [14,15] supports a recessive effect (amino acids NN vs. T/−; genotypes AA vs. C/−), the present study has only 41% power to detect the effect size (OR 1.24) detected by Hamid and colleagues in unselected cases [14]. However, once again, allowance for the effects of case selection leads to power estimates of >99.9% for detection of the OR seen in the Danish early onset case subset (OR=1.99), or, more conservatively, 97% for an OR of 1.50.…”
Section: Powermentioning
confidence: 98%
See 1 more Smart Citation
“…There are, however, examples of well-powered studies implicating the TNF region, in particular in myocardial infarction, 3 but this too has been followed by non-replication. 11 A previous study examining TNF variation in a large coronary heart disease (CHD) sample provided only weak evidence of an effect upon TNF plasma levels (in contrast to the above cited examples of ACE etc). 12 Against this background, we have performed a systematic evaluation of quantitative traits typically examined in cardiovascular disease, providing a broader search for phenotypes that may be able to detect the presence of functional variation within the TNF region.…”
Section: Introductionmentioning
confidence: 99%
“…The inflammatory cytokines lymphotoxin-α (LTA) and TNF-α play multiple roles in the development and function of the immune system and several studies have reported associations between these cytokines and insulin resistance [1]. In support of a role for LTA in the pathogenesis of metabolic traits, common genotypes of LTA have been shown to be associated with traits of the metabolic syndrome, type 2 diabetes and myocardial infarction [2][3][4][5] However, LTA and TNF-α are homologous, and their genes are in significant linkage disequilibrium (LD) [6]. LTA and TNF are also in LD with the extensive HLA cluster.…”
Section: Introductionmentioning
confidence: 99%